Al2O3 nanoparticles promote secretion of antibiotics in Streptomyces coelicolor by regulating gene expression through the nano effect. (July 2019) - Liu, Xiaomei; Tang, Jingchun; Wang, Lan; Giesy, John P.
Abstract: Toxic effects of nanoparticles (NPs) on microorganisms have attracted substantial attention; however, there are few reports on whether NPs can affect the secondary metabolism of microbes. To investigate the toxic effects of Al2 O3 NPs on cell growth and antibiotic secretion, Streptomyces coelicolor M145 was exposed to Al2 O3 NPs with diameters of 30 and 80 nm and bulk Al2 O3 at concentrations up to 1000 mg/L. The results indicated that differences in the toxicity of Al2 O3 NPs were related to the particle size. In treatment with Al2 O3 NPs, the maximum yields of undecylprodigiosin (RED) and actinorhodin (ACT) were 3.7- and 4.6-fold greater than that of the control, respectively, and the initial time of antibiotic production was much shorter. ROS quenching experiment by N-acetylcysteine (NAC) confirmed that ROS were responsible for the increased RED production. From 0 to 72 h, ROS had a significant impact on ACT production; however, after 72 h, the ROS content began to decrease until it disappeared. During ongoing exposure (0–144 h), ACT production continued to increase, indicating that in addition to ROS, nano effect of Al2 O3 NPs also played roles in this process. Transcriptional analysis demonstrated that Al2 O3 NPs could increase the expression levels of antibiotic biosynthetic genes and two-component systems (TCSs) and inhibit the expression levels of primary metabolic pathways. This study provides a new perspective for understanding the mechanisms of antibiotic production in nature and reveals important implications for exploring other uses of NPs in biomedical applications or regulation of antibiotics in nature. Graphical abstract: Image 1 Highlights: It is the first report NPs had effects on antibiotic production of S. coelicolor. 1000 mg/L Al2 O3 NPs resulted in 3.7 and 4.6-fold enhance production of RED and ACT. Al2 O3 NPs could increase the expression levels of antibiotic biosynthetic genes. Effects of NPs on antibiotic secretion are attributed by the nano effect.